Diagnostic Accuracy of Interferon-Gamma Release Assays for Tuberculous Meningitis: A Systematic Review and Meta-Analysis - Wen, An; Leng, Er-Ling; Liu, Shi-Min; Zhou, Yong-Liang; Cao, Wen-Feng; Yao, Dong-Yuan; Hu, Fan (Frontiers in Cellular and Infection Microbiology, 2022)
Aims:To evaluate and compare diagnostic accuracy of blood and cerebrospinal fluid interferon-gamma release assays (IGRAs) for diagnosing tuberculous meningitis (TBM), and review relevant literature.Main methods:We searched several databases including Medline,Embase,Cochrane databases and Chinese databases to identify studies published before 2021. All studies with QuantiFERON-TB Gold In-Tube and/or T-SPOT.TB (ELISPOT) assays of blood and/or cerebrospinal fluid (CSF), which complied with the Guidelines for the Quality Assessment of Diagnostic Accuracy Studies, were included.Quality of the included studies was assessed by using the revised Quality Assessment for Studies of Diagnostic Accuracy (QUADAS-2) method.Begg’s funnel plots were used to evaluate publication biasin the meta-analysis of diagnostic studies and statistical analysis was performed by using Stata (Version 12) software.Key findings:Twelve studies with blood and/or CSF IGRAs including 376 samples in patient group and 493 in the control group were included. The sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and area under summary receiver operating characteristic curve (SROC)of the blood IGRAs in the pooled data from 12 studies were 74% (95% CI: 0.65-0.82), 78% (95% CI: 0.68-0.86), 3.38 (95% CI 2.26-5.06), 0.33 (95% CI: 0.23-0.46), 10.25 (95% CI: 5.46-19.25), and 0.83 (95% CI: 0.79-0.86), respectively. For cerebrospinal fluid IGRAs, these values for the pooled data from the 10 studies included were 79% (95% CI: 0.71-0.85), 95% (95% CI: 0.88-0.98), 16.30 (95% CI 6.5-40.83), 0.22 (95% CI: 0.16-0.31), 57.93 (95% CI: 22.56-148.78),and 0.91 (95% CI: 0.88-0.93), respectively.Significance: Cerebrospinal fluid IGRAs exhibited a better diagnostic accuracy than blood IGRAs in diagnosing TBM.